Education on Limiting Sugar Consumption as an Effort to Maintain Balanced Nutrition in Adolescents at SMP N 51 Pekanbaru - Jumaydi, Zikhri; Dinda, Aulia Rahma; Melani, Dela; Intani, Felicia Putri; Amaliah, Hanifah; Fitri, Rahayu Annisa; Trianti, Rana Roidah; Nadila, Roja; Muzaidan, Saltsabillah; Shilaisna, Ulfa (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Adolescents tend to consume more sugar than other age groups. The habit of consuming sweet drinks needs special attention in public health considering its significant contribution to increasing blood sugar levels and body weight, including adolescents at SMP N 51 Pekanbaru. The purpose of community service is to improve the knowledge, attitudes, and actions of adolescents at SMP N 51 Pekanbaru in limiting sugar consumption as an effort to maintain balanced nutrition. Community service activities are carried out by providing education through lecture methods using power points . Educational activities result in an increase in the level of knowledge and attitudes in limiting sugar consumption, while there is no increase in actions in limiting sugar consumption after being given education, this occurs because of the difficulty in conducting counseling outdoors because the power point displayed cannot be seen clearly by all participants .